Outcomes and Patterns of Healthcare Utilization After Hospitalization for Pediatric Critical Illness Due to Respiratory Failure*. Issue 2 (February 2019) - Yagiela, Lauren M.; Barbaro, Ryan P.; Quasney, Michael W.; Pfarr, Marie A.; Ursu, Dan C.; Prosser, Lisa A.; Odetola, Fola O.
Abstract : Objectives: To quantify home care needs, healthcare utilization, and 2-year mortality after pediatric critical illness due to respiratory failure, and evaluate the impact of new morbidity and abnormal function at hospital discharge on resource use and outcomes. Design: Retrospective cohort study. Setting: Quaternary care PICU. Patients: Patients less than or equal to 18 years with respiratory failure from January 1, 2013, to December 31, 2014. Measurements and Main Results: Patient demographics, hospitalization characteristics, and healthcare utilization were quantified and compared according to morbidity development and discharge functional status. Multivariable regression methods evaluated 2-year readmission rates and mortality by morbidity development and discharge functional status. Of 163 patients, the median age was 2.1 years (interquartile range, 0.6–10.9 yr), 61 (37.4%) had a comorbidity, and 73 (44.8%) had abnormal function at admission. Median ventilation duration was 6.0 days (interquartile range, 3.0–11.7 d), and median PICU and hospital length of stay were 8 (interquartile range, 4–15) and 14 days (interquartile range, 8–23 d), respectively. At hospital discharge, eight of 163 (4.9%) had died, and 14 of 163 (8.6%) had a new morbidity. Of the surviving 155 patients at hospital discharge, 87 (56.1%) had abnormal function, 120 (77.4%) had new medications, 24 (15.5%) had new medical devices, and 43 (27.7%) had new home care equipment. Cumulative 2-year mortality was 14 of 163 (8.6%) with six of 163 (3.7%) occurring after discharge. Within 2 years, 81 of 155 of patients (52.2%) were readmitted, often (58/81, 71.6%) to the PICU. Abnormal function at discharge was associated with elevated odds of readmission to the hospital (odds ratio, 1.49; 1.28–1.74; p < 0.0001) and PICU (odds ratio, 1.47; 1.27–1.71; p < 0.0001) within 2 years. Conclusions: After critical illness, children have significant new healthcare burdens heretofore unrecognized. Abnormal functional status at hospital discharge was associated with increased healthcare utilization up to 2 years thereafter. Abstract : Supplemental Digital Content is available in the text.